THE SOCIAL WORK QUALITY DILEMMA - Švedaitė-Sakalauskė, Birutė (Socialinė teorija, empirija, politika ir praktika, 2007)
The goal of the paper is to analyze the social work quality dilemma. The essence of the dilemma is the impossibility to set up the measurable standards for social work quality. There are several reasons for dilemma. The interest groups demand for different standards. The local context needs the adaptation to the specificity of location. Introducing business logic into social sphere rise conflicts. The complexity of social work action and quality. The author proposes three conditions under which the problem of social work dilemma can be solved.
Keywords: Quality; Social work; Lithuania